Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The question here is to solve $x^2p+y^2q+z^2=0$ passing through a given curve $\Gamma : xy=x+y,z=1$

I am trying to solve it by Lagrange's method, where $\frac{dx}{x^2}=\frac{dy}{y^2}$, thus I get $1/y-1/x =c$ and then I substituted $x+y$ in place of $xy$ in denominator.

Thus I found: $(x-y)/(x+y)=c$

Is it correct ?

Soham

share|improve this question
add comment

1 Answer 1

You are looking for $z$ as a function of $(x,y)$. The idea is to think of the graph of $z(x,y)$ as built up from curves starting from $\Gamma$. Say we parametrize the curves as $(x(s,x_0),y(s,x_0),z(s,x_0))$ which start from $\Gamma$ at $s=0$, at the point $(x_0,y_0,z_0)$, where $z_0 = 1$ and $x_0 y_0 = x_0+y_0$ i.e. $1/x_0+1/y_0 = 1$. Then take the PDE to be a case of the chain rule $$ z' = z_x x'+z_y y' = x^2z_x+y^2z_y=-z^2 $$ where we take $x'=x^2$, $y'=y^2$, and $z' = -z^2$ with initial values as above. Solve these by separation of variables, integrating $x^{-2}x'=1$ and so forth, as $$\frac{1}{x}-\frac{1}{x_0}=-s, \ \ \frac{1}{y}-\Big(1-\frac{1}{x_0}\Big)=-s, \ \ \frac{1}{z}-1=s.$$ Add the first two to eliminate $x_0$, giving $1/x+1/y-1=-2s$. Then this is $-2\big(1/z-1\big)$, so you find $$z(x,y)=\frac{1}{\frac{3}{2}-\frac{1}{2y}-\frac{1}{2x}}$$This is a solution if you check it.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.